LITERATURA FANTÁSTICA ENTRE EL DIARIO CRÍTICA Y LA EDITORIAL SUDAMERICANA: POLÍTICAS EDITORIALES, MATERIALIDAD DE LOS TEXTOS Y MODOS DE ESCRITURA. - de los Ángeles Mascioto, María (Revista Chilena de Literatura, 2016)
This paper analizes changes in material and textual form experimented by a group of texts published and read in three different edition contexts (Revista Multicolor de los Sábados, Critica's Cultural and Litterary Supplement, and two different editions of Antología de la Literatura Fantástica, compiled by Jorge Luis Borges, Adolfo Bioy Casares y Silvina Ocampo, 1940 & 1965). At the same time, this work studies the way in which those changes affected the significance of the texts. We propose the hypothesis that a part or literary renovation promoted by Antología de la Literatura Fantástica has been tested in the thirties decade in the context of Critica's Litterary Supplement. The successive editions of those stories have involved a revission of both writing texts and the place that was given to fantasy and how this genre was presented to readers.